HYPERTENSION AND RISK FACTORS: A CASE CONTROL STUDY - Lumbangaol, Fernando; Handani, Myrnawati Crie; Sinaga, Taruli Rohana; Manurung, Kesaktian; Manurung, Jasmen (Jurnal Ilmiah Keperawatan, 2023)
Hypertension is a global health issue. It is the leading cause of morbidity and mortality. Therefore, the management and reduction of risk factors are essential to prevent and control the incidence of hypertension. The research aims to find out the risk factors associated with the incidence of hypertension in Puskesmas Matiti, Humbang Hasundutan District. This study is a correlation analytic study with a case control approach.. The population case is all the people with hypertension and the population control is the people without hypertension at Puskesmas Matiti. The research samples are composed of 32 people with hypertension and 64 people without hypertension. The samples are obtained using simple random sampling technique. Data are collected using questionnaires and analyzed using logistic regression test. The result indicates that sodium consumption (0.007<0.05) and obesity (0.025<0.05), both have a significant correlation with the incidence of hypertension. While smoking (0.054>0.05) and alcohol consumption (0.558>0.05), both have no significant correlation with hypertension incidence. The research concludes that the risk factors associated with the incidence of hypertension in Puskesmas Matiti are sodium consumption and obesity, with sodium consumption being the dominant factor. It is recommended to practice a healthy lifestyle by limiting the consumption of high sodium foods and maintaining the ideal weight by exercising and maintaining a healthy diet.